2019
DOI: 10.1097/psy.0000000000000695
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive Disorders of Pregnancy and Symptoms of Depression and Anxiety as Related to Gestational Age at Birth: Findings From the All Our Families Study

Abstract: Objective The aim of the study was to investigate whether symptoms of depression or state anxiety changed the strength or nature of the association between hypertensive disorders of pregnancy (HDP) and gestational age at birth. Methods We conducted a secondary analysis of data from the All Our Families Cohort, a prospective pregnancy cohort study based in Calgary, Alberta, Canada. Self-reported depressive symptoms and state anxiety were assessed between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Most of the high-risk pregnancies in our study were hypertensive diseases of pregnancy (29.5 %) and gestational and pregestational diabetes (25 %). Previously, it has been shown that anxiety rate increases in hypertensive disease of pregnancy, and gestational and pregestational diabetic women [24][25][26]. Our results support this finding in the sense that during the COVID-19 pandemic, compared to normal pregnancies anxiety is much higher in the high-risk pregnancy patients.…”
Section: Discussionsupporting
confidence: 89%
“…Most of the high-risk pregnancies in our study were hypertensive diseases of pregnancy (29.5 %) and gestational and pregestational diabetes (25 %). Previously, it has been shown that anxiety rate increases in hypertensive disease of pregnancy, and gestational and pregestational diabetic women [24][25][26]. Our results support this finding in the sense that during the COVID-19 pandemic, compared to normal pregnancies anxiety is much higher in the high-risk pregnancy patients.…”
Section: Discussionsupporting
confidence: 89%
“…Anxiety and depression are the main manifestations of psychological stress of primipara in late pregnancy. Although, appropriate psychological stress can improve the individual's alertness and adaptability [ 9 ]. However, long-term intense psychological stress can damage people's social function, reduce the body's resistance, and affect normal physical and mental health [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The links between mental health and obstetrical outcomes is an emerging area, and there is increasing evidence that there may be a cumulative impact of depression and/or anxiety on negative obstetrical outcomes. Specifically, studies have suggested that pregnant women with a diagnosis of anxiety in addition to hypertension are at higher risk of preterm delivery than women with hypertension alone (Hilmert et al, 2008;Horsley et al, 2019). Fortunately, clinical interventions such as cognitive behavioral therapy during pregnancy have been demonstrated to effectively prevent and reduce prenatal depression and anxiety (Curry et al, 2019;Marchesi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal depression and/or anxiety are risk factors for a number of obstetric complications and strong predictors of postpartum mental health problems (Alder, Fink, Bitzer, Hösli, & Holzgreve, 2007; Underwood, Waldie, D'Souza, Peterson, & Morton, 2016). Emerging evidence suggests that the combination of both an HDP and elevated symptoms of depression or anxiety during pregnancy further increases the risk of adverse obstetrical outcomes including lower birth weight and lower gestational age at birth (Hilmert et al, 2008; Horsley, Tomfohr-Madsen, Ditto, & Tough, 2019), with one recent study reporting that reduced gestational age is associated with HDP at all percentiles of self-reported depression or anxiety symptoms (Horsley et al, 2019). Psychosocial factors such as chronic stress and elevated symptoms of depression and anxiety have been shown to precede development of hypertension in the general population, and there are indications that similar associations are present in pregnancy (Cuevas, Williams, & Albert, 2017; Meng, Chen, Yang, Zheng, & Hui, 2012; Yan et al, 2015; Zhang et al, 2013).…”
mentioning
confidence: 99%